New Tools in HCV Diagnosis, in Light of the Enhanced Awareness and the New Drugs for Treatment: SMARTube and Stimmunology - Svetlana Gorodin; Serhat Unal; Youchun Wang; Mikhail I. Mikhaylov; Ludmila Bigbulatova; Tamar Jehuda-Cohen (The Scientific World Journal)
With improved HCV therapy, challenges regarding HCV diagnosis, such as seronegative window period, false positive readings, and differentiation between recent, chronic, and resolved infections, are of increasing importance. To address these challenges an innovative device—SMARTube HIV & HCV—was used. Blood samples were tested for anti-HCV antibodies before and after incubation in the SMARTube, which promotes the in vitro stimulation of in vivo HCV primed lymphocytes, thus enhancing levels of anti-HCV antibodies. Comparing antibody levels, in concordant samples before and after SMARTube, yielded the Stimulation Index (SI). Among 5888 fresh blood samples, from various populations and regions worldwide, 641 were seropositive using plasma, while SMARTube processing (yielding enriched plasma, termed SMARTplasma) enabled diagnosis of 10 additional carriers in high-risk cohorts, that is, earlier detection. Using SMARTplasma eliminated all false positive results, using the current assays. In addition we show that SI calculation may serve as an important tool for differentiating between those who recently seroconverted, carriers of long-term infection, and those who have cleared the virus. SMARTube and the SI could lead to better, more informative diagnosis of HCV infections and play an important role in changing the way we treat both the infected individuals and the epidemic as a whole.